Effect of Transfer Layer on Ultra Low Friction of CNx Coating under Blowing Dry Ar - Nor Azmmi Bin Masripan (Japanese Society of Tribologists, 2013)
In order to clarify the ultra low friction mechanism of Carbon Nitride (CNx) coatings under blowing dry Ar, thickness and area of transfer layers on mating surface were in-situ observed with an optical microscope during sliding against a sapphire hemisphere under blowing dry Ar. During sliding, thickness of transfer layer from CNx coating to a sapphire hemisphere increased and leaded to ultra low friction. When thickness and area of transfer layer was thick and small respectively, ultra low friction was observed. The result showed that the coefficient of friction decreased from 0.18 to 0.003 and remained constant throughout the friction test. It was confirmed the formation of a graphite-like transfer layer with Raman analysis and Auger Electron Spectroscopy (AES).